Spatial distribution of soil morphology and physicochemical properties to assess land degradation under different NDVI and TRI in North Halmahera, Indonesia - Rofita Rofita; Sri Nuryani Hidayah Utami; Azwar Maas; Makruf Nurudin (Journal of Degraded and Mining Lands Management, 2021)
Land degradation is currently a major environmental problem that can lead to decreasing biomass productivity. The causes of land degradation have been widely reported. However, the soil morphological characteristics and its detailed properties related to land degradation need to be investigated further. The research was conducted in North Halmahera Regency in March-April 2020. The study started with an overlay of basic maps such as rainfall, land use, topography, and soil types to map the degraded land units. Several land units classified from slightly damaged to severely damaged will be validated based on field observations and supported by laboratory measurements. Characterization of soil morphology and soil sampling was carried out according to USDA international standards. Sentinel 2A image and SRTM image from March to April 2020 were used to determine NDVI and TRI. The characteristics of the soils that have not been degraded tend to be found in volcanic landscapes, while those of the degraded soils tend to be found in structural and karst hills. The thickness of the degraded soil horizons tends to be shallower with an incomplete horizon arrangement, and many rock fragments are found in the soil surface layer. SOC gradually decreases in degraded soils, while the essential nutrients (N, P, and K) are relatively more varied across soil types. The improper land use without conservation on steep slopes causes the soils to be easily degraded. The soil degradation index has a linear relationship with NDVI and TRI. Thus, the revitalization of degraded lands needs to pay attention to the layout and types of vegetation with different slope levels according to the geomorphological zone.